1986
DOI: 10.1093/infdis/153.3.593
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Investigation of the Intracellular Bioactivity of Amoxicillin, Clindamycin, and Erythromycin for Staphylococcus aureus

Abstract: The intraphagocytic bioactivities for Staphylococcus aureus of amoxicillin, clindamycin, and erythromycin (0.0075-20 micrograms/ml) were measured in human polymorphonuclear leukocytes (PMNLs) with the combination of a fluorochrome microassay and a radioassay. PMNLs with normal or depleted membrane-associated oxidative metabolism were used to investigate the interactions that may occur between the intrinsic O2-dependent antimicrobial systems of human phagocytes and antimicrobial agents in the elimination of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Only a few authors [5,7,9,[30][31][32][33] have used PMNLs from patients with defective respiratory burst, and have found that the intraphagocytic activity of antimicrobial agents was less efficient in these PMNLs.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few authors [5,7,9,[30][31][32][33] have used PMNLs from patients with defective respiratory burst, and have found that the intraphagocytic activity of antimicrobial agents was less efficient in these PMNLs.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable example is the apoptosis of macrophages induced by pathogens such as Shigella, which both avoid the antibacterial effect of those cells and trigger inflammation (427,428). In some well-characterized examples, bacteria are able to travel from cell to cell without any significant contact with the extracellular milieu (43,273), thus avoiding the immune system as well as contact with antibiotics that do not enter mammalian cells (12,172). This provides the first clue as to how well-characterized virulence phenotypes can be related to antibiotic resistance.…”
Section: Common Mechanisms Involved In Virulence and Resistancementioning
confidence: 99%
“…Mammalian cells are poorly permeable to or easily exclude several families of antibiotics (12,166). Even if the antibiotic enters the mammalian cells, intracellular growth might induce a transient antibiotic-resistant phenotype, a situation that has been described for Legionella pneumophila (35).…”
Section: Common Mechanisms Involved In Virulence and Resistancementioning
confidence: 99%
“…In vitro, the elution of the macrolides out of the phagocytes is very rapid (within minutes) once the extracellular drug is removed (13). Several investigators have shown that 14-membered macrolides can significantly impair oxidative metabolism of the neutrophils in vitro, as assessed by luminolenhanced chemiluminescence, superoxide generation, H202 and OH-production, and myeloperoxidase-mediated iodination of proteins (1,3,11,18,21). Inhibition occurred at fairly high concentrations (50 mg/liter for roxithromycin and erythromycin) and was reversible by washing the cells (18).…”
mentioning
confidence: 99%